Makerspace sound and music projects for all ages - Glendening, Mary L.; Glendening, Isaac W. (New York McGraw-Hill Education, 2018)
"This easy-to-follow guide shows, step-by-step, how to work with sound generation, recording, editing, and distribution tools. Co-written by a professional audio engineer and a dedicated maker-librarian, Makerspace Sound and Music Projects for All Ages gets you started designing, programming, and assembling fun music and audio creations right away. The book features dozens of DIY projects complete with parts lists, start-to-finish instructions, and full-color illustrations that guarantee success. You will explore the latest inexpensive--or free!--audio software for Windows, Apple, iOS, and Android devices."--Provided by publisher.
Includes index.
Keywords: Sound -- Recording and reproducing -- Amateurs' manuals; Makerspaces; Music videos -- Production and direction